Intergenerational Transmission of Abusive Parenting: Role of Prospective Maternal Distress and Family Violence. (May 2021) - Morelli, Nicholas M.; Duong, Jacqueline; Evans, Meghan C.; Hong, Kajung; Garcia, Jackelyne; Ogbonnaya, Ijeoma N.; Villodas, Miguel T.
Parents who were abused as children are at increased risk for perpetuating maladaptive parenting practices, yet the mechanisms underlying this relationship remain unclear. This study prospectively examined maternal distress (a latent variable consisting of depressive symptoms and daily stress) and family violence as potential mediators in the intergenerational transmission of abusive (i.e., psychologically aggressive and physically assaultive) parenting. Participants included ( N = 768) mother-child dyads identified as being at-risk for family violence and maltreatment prior to children's age four. More maternal childhood abuse was associated with more distress and increased risk for family violence exposure in adulthood. However, only maternal distress mediated the association between mothers' history of abuse and their use of abusive parenting strategies. This study provides critical information about ecological mechanisms underlying the intergenerational transmission of abusive parenting and suggests the importance of targeting depression and stress management among mothers with abuse histories to curtail the cycle of violence.